The Influence of Instagram Marketing on Colleges on Post Interaction - Nilam Ratna Nur Widadasari; Majang Palupi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to determine the extent to which Self-Efficacy, Ethical Leadership and Innovative Work Behavior influence Work Engagement at the Information Systems Agency (BSI) UII. The research approach used by this researcher uses a quantitative method. This research was conducted at the Information Systems Agency (BSI) of the Islamic University of Indonesia. The population in this study were all employees at BSI UII. The sample used in this study was taken using the census technique, namely taking all objects that are members of the population as study or observation materials with a total of 104 employees. The data analysis technique used was hypothesis testing using smart PLS. The results of this research show that there is a significant positive influence between ethical leadership on work engagement. There is a significant positive influence of innovative work behavior on work engagement. There is no significant influence between ethical leadership and self-efficacy. There is a significant positive influence of innovative work behavior on self-efficacy. There is a significant positive influence of self-efficacy on work engagement. There was no significant influence between ethical leadership and work engagement mediated by self-efficacy. There is a significant positive influence between innovative work behavior on work engagement mediated by self-efficacy.